Validity and reliability of impact forces from a commercially instrumented water-filled punching bag - Diewald, S. N.; Cross, M. R.; Neville, J.; Cronin, J. B. (Sports Engineering, 2022)
Measuring striking forces is important to provide actionable insight for training and performance enhancement for combat sport athletes. Recent technology may provide a low-cost solution to an otherwise complicated kinetic assessment. The aim was to assess the reliability and validity of a water-filled training bag and integrated sensor for measuring peak impact force. A pendulum design was used to swing a range of known mass loads (kettlebells) from various heights to impact a stationary 21" Aqua Training Bag®. For each condition, the momentum of the mass at impact was calculated and compared with the measured impact force from a pressure sensor affixed to the side of the water-filled bag. Peak impact force was strongly associated with calculated momentum (r(18) = 0.96 [0.91, 0.99], p < 0.001), with a high degree of shared variance (92.7%, F(1,18) = 229.9, p < 0.001). There was almost perfect agreement for all reliability loading conditions (ICC = 0.995-0.999) and typical error was = 5% (CV = 3.3-5.1). Impact kinetics from the sensor appear to be reliable and valid and may be integrated into practice and research. However, the utility of the instrumented bag for striking kinetics of athletes, and thus practical utility when used in the field, requires further investigation.